2020
DOI: 10.1111/csp2.285
|View full text |Cite
|
Sign up to set email alerts
|

Species and demographic responses to wildlife‐friendly fencing on ungulate crossing success and behavior

Abstract: Fencing is a ubiquitous part of the landscape across the Great Plains of North America. This can fragment habitats and reduce the ability of wildlife to move between patches. A relatively novel conservation tool aimed at mitigating these impacts is the use of wildlife‐friendly fencing. However, there is still an incomplete understanding as to how this tool affects ungulate movement and whether it increases habitat connectivity across barriers. Using camera trap data from three properties across the American Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Also, fences are built for specific species and purposes, and often achieve those purposes, although their effects on non‐target species can create losers 10 . Nowadays, a relatively novel conservation tool aimed at mitigating these impacts is the use of wildlife‐friendly fencing 74 . However, there is still an incomplete understanding as to how this tool affects, the movement of animals, and whether it increases habitat connectivity across barriers and future studies must fill these gaps.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, fences are built for specific species and purposes, and often achieve those purposes, although their effects on non‐target species can create losers 10 . Nowadays, a relatively novel conservation tool aimed at mitigating these impacts is the use of wildlife‐friendly fencing 74 . However, there is still an incomplete understanding as to how this tool affects, the movement of animals, and whether it increases habitat connectivity across barriers and future studies must fill these gaps.…”
Section: Discusionmentioning
confidence: 99%
“…10 Nowadays, a relatively novel conservation tool aimed at mitigating these impacts is the use of wildlife-friendly fencing. 74 However, there is still an incomplete understanding as to how this tool affects, the movement of animals, and whether it increases habitat connectivity across barriers and future studies must fill these gaps.…”
Section: Drawbacks Of Fencesmentioning
confidence: 99%
“…This finding is similar to previous studies, which found the number of crossing attempts increased for some species after modifications to existing fences, such as the addition of smooth (non‐barbed) bottom wire or clips to elevate the bottom wire (Burkholder et al, 2018 ; Jones et al, 2018 , 2020 ). These wildlife‐friendly modifications with elevated bottom wire and smooth wire may also reduce the time for species to cross and increase the probability of successful crossings of wildlife, and effectively enclose livestock (Segar & Keane, 2020 ). We occasionally observed deer and nilgai use fence crossings at a full sprint; it seems likely the animals were familiar with and had previously used the crossing locations.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that there are a variety of effective options for such. Gaps can be installed to be selective for certain species (e.g., exclusion of rhinos by rock walls: Dupuis-Désormeaux et al, 2016; exclusion of livestock by tubular metal grills: Gates et al, 2012; selective fence designs: Laskin et al, 2020;Segar and Keane, 2020) or simply open for all species. Animals will incorporate them into their movement corridors over time (Dupuis-Desormeaux et al, 2018).…”
Section: Management Implications and Future Perspectivementioning
confidence: 99%